Social media using by teenagers: potential impact on psychic and behavior - Ogorenko, Вікторія; Tymofieiev, Роман; Haribova, Лейла; Kramarchuk, Дмитро; Shornikov, Андрій (Psychosomatic Medicine and General Practice, 2024)
Actuality. The growing use of social networks forces us to pay attention to their impact on the mental health of children and adolescents. Excessive use can cause a variety of problems, such as mood disorders, social comparison, anxiety disorders, eating disorders, alcohol use, self-harm, and cyberbullying. There is a need to develop effective strategies for preventing and treating these problematic phenomena. Work to prevent these problems includes developing strategies for parents, teachers and other adults to educate children about social media use. This can include limiting the time spent on social media, educating about online safety, and encouraging healthy online habits. The work aimed to analyze the potential hazards associated with the excessive use of social media among secondary school students. Additionally, the research aimed to identify any potential risks and problems that may arise as a result of their online behavior. Materials and methods. We interviewed 41 schoolchildren aged 12 to 16 (39% boys and 61% girls) who participated in the survey to determine their online habits and mental health status. Results. Almost every fourth teenager notes that he spends more time on the Internet than he would like. More than 70% of respondents may neglect household chores or studies to spend more time online; 26.8% always or often prefer being online to communicating with loved ones. It is noteworthy that 17.1% had suicidal thoughts. The model that included age, presence of panic attacks, and presence of family dissatisfaction with excessive Internet use had the best predictive power for predicting suicidal thoughts and tendencies, for which the AUC was 0.947 (95% CI 0.829–0.993). The sensitivity of the obtained model was 85.71%, specificity - 91.18%. Conclusions. Thus, the presence of panic attacks in the past increases by 211.75 (95% CI 3.17–14165.93) times the chances of suicidal thoughts and tendencies, the presence of relatives' dissatisfaction with excessive use of the Internet by 9.5 (95% CI 1, 27 – 71.27) times, and the increase in age – 5.95 (95% CI 1.42 – 24.94) times.